(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article explores the significance of teaching English for Specific Purposes (ESP) in today’s globalized world. It emphasizes how ESP addresses the unique linguistic needs of professionals and students in specialized fields, enhancing workplace competence and academic success. By focusing on relevant, field-specific language, ESP provides learners with the practical skills necessary for effective communication in their chosen domains.